أثر القواعد النحوية في إبراز الفروق اللغوية دراسة وصفية: The effect of grammatical rules in highlighting linguistic differences: descriptive study - Rabea Mohamed Mohamed Hefny; Mohamed Chourana (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
ملخص تحديد الفروق الدلالية بين ألفاظ اللغة يحتاج إلى معايير علمية محددة، هذه المعايير يجب أن تكون متسقة مع خصائص لغتنا العربية، ومستمدة من قواعدها، كي نستطيع باتباعها الوقوف على السمات الدلالية المميزة لكل لفظ، وقد استعان اللغويون العرب بالقواعد النحوية لإبراز الفروق الدلالية بين الألفاظ المتقاربة المعنى، فإلى أي مدى بلغ معيار القواعد النحوية دقة وشمولا؟ وما الصعوبات التي تواجهنا عند تطبيق هذا المعيار؟ البحث الذي بين أيدينا يقدم وصفا وتحليلا دلاليا لتلك المعايير المنبسقة من القواعد النحوية بغية الإجابة عن هذه التساؤلات، وقد أسفر البحث عن نقاط القوة والضعف في معايير القواعد النحوية المستعملة في إظهار الفروق اللغوية بين الألفاظ المتقاربة المعنى، وحدد الإشكالات التي تقف دون فاعلية هذه المعايير عند التطبيق، وانتهى إلى توصيات عملية لاستثمار معايير القواعد النحوية على الوجه الأمثل. الكلمات المفتاحية: القواعد النحوية-الفروق اللغوية-الترادف-معايير دلالية Abstract Determining the semantic differences between the words of the language requires specific scientific criteria. These criteria must be consistent with the characteristics of our Arabic language, and derived from its rules, so that by following them we can identify the distinctive semantic features of each word. Arab linguists have used grammatical rules to highlight the semantic differences between convergent words. Meaning, how accurate and comprehensive is the grammatical standard? What are the difficulties we face when applying this standard? The research in our hands provides a semantic description and analysis of those grammatical criteria in order to answer these questions, and the research has resulted in the strengths and weaknesses in the grammatical criteria criteria used to show the linguistic differences between words of close meaning, and identify the problems that stand in the absence of the effectiveness of these criteria when The application, and ended with practical recommendations for the optimal investment of grammar standards. Keywords: Grammar Rules, Linguistic Differences, Synonyms, Semantic Criteria Semantic Criteria